Fetal reduction from twin to singleton gestation: A meta‐analysis. Issue 2 (22nd November 2021) - Bardin, Ron; Gupta, Mamta; Greenberg, Gal; Nandrajog, Anchal; Tenenbaum‐Gavish, Kinneret; Gupta, Nikhil; Perlman, Sharon; Shmueli, Anat; Hadar, Eran
Abstract: Objective: To evaluate outcomes of fetal reduction in twin pregnancy. Search strategy: PubMed, EMBASE, Cochrane Central Register of Controlled Trials, and Google Scholar were searched from 1980 through December 2020. Selection criteria: Prospective or retrospective studies of pregnant women with twin gestations who had a transabdominal reduction of twin to singleton pregnancy with a comparison group of ongoing twin gestations. Data collection and analysis: Outcomes were meta‐analyzed only if reported in at least three studies. Main results: Six studies with a pooled sample of 2867 women with a twin pregnancy of whom 624 underwent 2‐to‐1 reduction and 2243 did not. In the fetal reduction group, the odds of preterm birth before 34 and 37 weeks of pregnancy were lower by 36% (odds ratio [OR] 0.64, 95% confidence interval [CI] 0.48–0.86, P  < 0.003) and 77% (OR 0.23, 95% CI 0.12–0.44, P  < 0.001), respectively, than in the control group, and the odds of hypertensive disorders and cesarean delivery were lower by 75% (OR 0.25, 95% CI 0.15–0.43, P  < 0.001) and 65% (OR 0.35, 95% CI 0.20–0.62, P  < 0.001), respectively. Conclusion: Twin reduction to singleton pregnancy decreased the possibility of preterm birth, hypertensive disorders in pregnancy and cesarean delivery. Sufficiently powered prospective studies are needed to support these findings. Abstract : Women with twin pregnancies undergoing fetal reduction had significantly lower odds of preterm birth, hypertensive disorders, and cesarean delivery than women with ongoing twin gestations.